Mild Cognitive Impairment: Structural, Metabolical, and Neurophysiological Evidence of a Novel EEG Biomarker - Moretti, Davide Vito (Frontiers in Neurology, 2015)
Background: recent studies demonstrate that the alpha 3/alpha 2 power ratio correlates with cortical atrophy, regional hypoperfusion and memory impairment in subjects with mild cognitive impairment (MCI). Methods: evidences were reviewed in subjects with MCI who underwent EEG recording, Magnetic Resonance Imaging (MRI) scans and memory evaluation. Alpha3/alpha2 power ratio (alpha2 8.9–10.9 Hz range; alpha3 10.9–12.9 Hz range), cortical thickness, linear EEG coherence and memory impairment have been evaluated in a large group of 74 patients. A subset of 27 subjects within the same group underwent also Single Photon Emission Computed Tomography (SPECT) evaluation. Results: in MCI subjects with higher EEG upper/low alpha power ratio a greater temporo-parietal and hippocampal atrophy was found as well as a decrease in regional blood perfusion and memory impairment. In this group, an increase of theta oscillations is associated with a greater interhemispheric coupling between temporal areas. Conclusion: the increase of alpha3/alpha2 power ratio is a promising novel biomarker in identifying MCI subjects at risk for Alzheimer’s disease